2019
DOI: 10.1002/mcda.1678
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the most suitable classification algorithm for supporting assistive technology adoption for people with dementia: A multicriteria framework

Abstract: The number of people with dementia (PwD) is increasing dramatically. PwD exhibit impairments of reasoning, memory, and thought that require some form of self‐management intervention to support the completion of everyday activities while maintaining a level of independence. To address this need, efforts have been directed to the development of assistive technology solutions, which may provide an opportunity to alleviate the burden faced by the PwD and their carers. Nevertheless, uptake of such solutions has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…From our analyses, we have demonstrated that the adapted TAM2 concepts of caregivers provide support for our hypotheses about care recipients' use of fall alert wearables, which is reflective of previous literature [12,[20][21][22][23][24][25]30]. Our model demonstrated that both high perceived usefulness and value of technology for caregiving was associated with greater interest in technologies for caregiving and that greater interest in technology for caregiving was predictive of greater use of fall alert wearables among care recipients, although only 28% (153/548) of our study's care recipients used fall alerts.…”
Section: Principal Findingssupporting
confidence: 80%
See 1 more Smart Citation
“…From our analyses, we have demonstrated that the adapted TAM2 concepts of caregivers provide support for our hypotheses about care recipients' use of fall alert wearables, which is reflective of previous literature [12,[20][21][22][23][24][25]30]. Our model demonstrated that both high perceived usefulness and value of technology for caregiving was associated with greater interest in technologies for caregiving and that greater interest in technology for caregiving was predictive of greater use of fall alert wearables among care recipients, although only 28% (153/548) of our study's care recipients used fall alerts.…”
Section: Principal Findingssupporting
confidence: 80%
“…We further based our analyses on specific demographic factors and caregiving contexts available from the data in our survey. In addition, our analyses were based on the following subhypotheses, supported in the literature: (1) younger age among caregivers would predict greater perceived usefulness, perceived value, and interest in using technology; (2) more demanding caregiving situations such as longer caregiving hours and dementia among care recipients would increase caregivers’ interest in technology; (3) older age among care recipients would predict greater health care needs and fall risks, hence more need for and use of fall alert–related technology [ 22 , 23 ]; and (4) use of or preference for using family (ie, unpaid) caregivers is most likely associated with economic status (ie, the ability to pay for caregivers) and the availability of unpaid caregivers as well as care recipients’ health conditions [ 23 , 24 ]. Correlates that predict the use of paid versus unpaid caregivers may also influence the use of fall alert technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ATS in health has been covered extensively with general approaches [13][14][15] and with approaches focusing on specific health problems such as visual impairment [16], disabilities [17,18], and dementia [3,[19][20][21][22][23]. This section provides an insight into recent relevant work in ATS for PwD, which has helped to identify similar approaches to the one presented in this paper, to which to compare to and learn lessons from.…”
Section: A Background On Assistive Technology Solutions (Ats) For Pwdmentioning
confidence: 99%
“…Nonetheless, technology solutions have been used to improve the quality of life of PwD, to support the work of carers, and to provide more personalized types of treatment. Assistive Technology-based Solutions (ATS) [3] have been commonly prescribed as a form of non-pharmacological treatment to PwD to help them complete everyday activities whilst maintaining a level of independence, yielding health and social benefits for them. Some of the areas in which ATS provide support include memory, mobility, indoor and outdoor safety, independence, and socializing.…”
Section: Introductionmentioning
confidence: 99%
“…We further based our analyses on specific demographic factors and caregiving contexts available from the data in our survey. In addition, our analyses were based on the following subhypotheses, supported in the literature: (1) younger age among caregivers would predict greater perceived usefulness, perceived value, and interest in using technology; (2) more demanding caregiving situations such as longer caregiving hours and dementia among care recipients would increase caregivers' interest in technology; (3) older age among care recipients would predict greater health care needs and fall risks, hence more need for and use of fall alert-related technology [22,23]; and (4) use of or preference for using family (ie, unpaid) caregivers is most likely associated with economic status (ie, the ability to pay for caregivers) and the availability of unpaid caregivers as well as care recipients' health conditions [23,24]. Correlates that predict the use of paid versus unpaid caregivers may also influence the use of fall alert technologies.…”
Section: Introductionmentioning
confidence: 99%